Mr. Lemoncello's Library Olympics - Grabenstein, Chris; Grabenstein, Chris (New York : Random House, 2016)
Welcome, boys and girls, readers of all ages, to the first-ever Library Olympiad! Kyle and his teammates are back, and the world-famous game maker, Luigi Lemoncello, is at it again! This time Mr. Lemoncello has invited teams from all across America to compete in the first ever LIBRARY OLYMPICS. Will it be fun? Like the commercials say ... HELLO? It's a Lemoncello! But something suspicious is going on ... books are missing from Mr. Lemoncello's library. Is someone trying to CENSOR what the kids are reading?! In between figuring out mind-boggling challenges, the kids will have to band together to get to the bottom of this mystery. Now it's not just a game -- can Mr. Lemoncello find the real defenders of books and champions of libraries?
Sequel to: Escape from Mr. Lemoncello's library (2013).
Includes bibliographical references (pages 272-275).
Ages 8-12.
Keywords: Libraries -- Juvenile fiction; Contests -- Juvenile fiction; Books and reading -- Juvenile fiction; Prohibited books -- Juvenile fiction; Children's literature -- Censorship -- Juvenile fiction; Libraries -- Censorship -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Libraries -- Fiction; Contests -- Fiction; Books and reading -- Fiction; Censorship -- Fiction; Eccentrics and eccentricities -- Fiction